2022
DOI: 10.3390/antiox11091662
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Metabolite Reuterin Attenuated LPS-Induced Oxidative Stress and Inflammation Response in HD11 Macrophages

Abstract: Reuterin is well-known for its broad-spectrum antimicrobial ability, while the other potential bioactivity is not yet clear. The present study aims to investigate the immunomodulatory activity of reuterin on chicken macrophage HD11 cells for the first time and evaluate whether reuterin is able to regulate the lipopolysaccharide-stimulated inflammatory response. The results showed that the safe medication range of reuterin was less than 250 μM. Reuterin treatment for 6 h decreased the transcriptional of CD86, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…The molecular mechanism might be explained by that reuterin can increase reactive oxygen species and thus reduce ribosomal biogenesis by selectively binding to cysteine residues, accompanied by increased gene expression downstream of nuclear factor erythroid-derived 2 (Nrf-2) (Bell et al, 2022). However, it was also revealed in vitro experiments that reuterin treatment at a dose of 250mM significantly suppressed LPS-induced oxidative stress by enhancing Nrf-2 expression and reducing reactive oxygen species production in HD11 macrophage cells (Xu et al, 2022). These data revealed that the effects of reuterin depend on certain cell types, reuterin concentration, and stimulation time.…”
Section: Reuterinmentioning
confidence: 82%
“…The molecular mechanism might be explained by that reuterin can increase reactive oxygen species and thus reduce ribosomal biogenesis by selectively binding to cysteine residues, accompanied by increased gene expression downstream of nuclear factor erythroid-derived 2 (Nrf-2) (Bell et al, 2022). However, it was also revealed in vitro experiments that reuterin treatment at a dose of 250mM significantly suppressed LPS-induced oxidative stress by enhancing Nrf-2 expression and reducing reactive oxygen species production in HD11 macrophage cells (Xu et al, 2022). These data revealed that the effects of reuterin depend on certain cell types, reuterin concentration, and stimulation time.…”
Section: Reuterinmentioning
confidence: 82%
“…HD11 cells in the logarithmic growth phase were resuspended in a completed medium at a concentration of 5 × 10 5 cells/mL and inoculated into a 6-well plate at 2 mL per well. After 24 h of culture, the cells were incubated with or without GML (10 μg/mL) for 12 h, followed by incubation with or without LPS challenge (2 μg/mL) for a further 12 h as previously described ( Xu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%